Mechanistic Insights into Heavy Metal Ion Adsorption by FeMgAl-Layered Double Hydroxide and Rice Husk Biochar Composite - Daniyal Durrani; Tasawar Abbas; Muhammad Muntazir Mehdi; Vaneeza Javed; Samn Tabassum, (Dialogue Social Science Review (DSSR), 2025)
Lead (Pb²⁺) and cadmium (Cd²⁺) ions are examples of heavy metals that are often found in water resources and which are environmentally persistent, toxic and capable of bioaccumulation. This work aims to understand the adsorption behaviour and processes of FeMgAl-LDH/RHB composite for the adsorption of these metal ions in aqueous media. The hydrothermal approach was employed towards the synthesis of a composite of LDH and biochar, so that synergistic improvement in the adsorption capacity and selectivity could be achieved. Surface characterization by SEM, EDS, and FTIR further confirmed the loading of the LDH onto the biochar network creating a material with enhanced porosity, surface chemistry and active sites. Fixed-batch adsorption studies exhibited fast adsorption rates with the adsorption process reaching equilibrium within 15 min for Pb²⁺ and Cd²⁺ respectively, and maximum adsorption capacity of 205.2 for Pb²⁺ and 108.4 for Cd²⁺. It was also revealed that the adsorption process depended on the pH and preferable pH was 6.0 for Pb²⁺ and 8.0 for Cd²⁺. The adsorption isotherm data fitted the Langmuir model, and the kinetics data analysis proposed the pseudo second order expression, which confirmed monolayer chemisorption as the primary super adsorption mechanism. Comparison with other works also showed the improved efficiency of the FeMgAl-LDH/RHB composite due to the strengthened structure and functions. The results therefore indicate that this composite holds practical application in the removal of heavy metals, a fitting application in wastewater treatment and environmentally relevant utilities. More studies are needed to fine tune synthesis, determine the feasibility of scale up, and enhance the regeneration process for practical use.